2012
DOI: 10.1039/c2ob06993h
|View full text |Cite
|
Sign up to set email alerts
|

(S)-Proline-catalyzed nitro-Michael reactions: towards a better understanding of the catalytic mechanism and enantioselectivity

Abstract: (S)-Proline-catalyzed nitro-Michael additions of aldehydes and ketones to β-nitrostyrene were investigated computationally (MP2/6-311+G**//M06-2X/6-31G**). Contrary to what is usually assumed in organocatalysis, the lowest-energy transition states of proline-catalyzed nitro-Michael reactions do not necessarily involve the carboxylic acid group of the proline moiety directing the incoming nitroalkene to the same face through hydrogen bonding. For the aldehyde substrates examined, the TS leading to the major (R,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…If the enthalpy (1.3 or 0.8 kcal/mol) is used for the calculation of the stereoselectivity, the prediction (79.9%ee or 58.8%ee) is even closer to the experimental result (46%ee), especially for the DBUH + -bound TS model. This is similar to the previous reports by Houk [35][36], Pápai [37], Sunoj [38], and Wong [39] et al where they have suggested that prediction based on enthalpy was more accurate than that based on free energy, mostly due to the lack of accuracy in entropy calculations involving low frequency vibrations in transition states. Surprisingly, in the gas phase, the trend for the stability order of the TSs involving intermediate II is different with that in solution phase, where the syn-s-trans mode (TS IIc) is favorable than the anti-s-cis mode (TS IIb).…”
Section: ð1þsupporting
confidence: 89%
“…If the enthalpy (1.3 or 0.8 kcal/mol) is used for the calculation of the stereoselectivity, the prediction (79.9%ee or 58.8%ee) is even closer to the experimental result (46%ee), especially for the DBUH + -bound TS model. This is similar to the previous reports by Houk [35][36], Pápai [37], Sunoj [38], and Wong [39] et al where they have suggested that prediction based on enthalpy was more accurate than that based on free energy, mostly due to the lack of accuracy in entropy calculations involving low frequency vibrations in transition states. Surprisingly, in the gas phase, the trend for the stability order of the TSs involving intermediate II is different with that in solution phase, where the syn-s-trans mode (TS IIc) is favorable than the anti-s-cis mode (TS IIb).…”
Section: ð1þsupporting
confidence: 89%
“…Proline acts as a nucleophilic catalyst in the Michael reaction by forming an enamine intermediate with the aldehyde. 20 Even though the reaction is commonly performed in organic solvents, the organocatalyzed Michael reaction is known to proceed in water. 21 Reaction conditions: 10 mM trans -β-nitrostyrene 8 , 100 mM butanal 9 , 10 mM P- 4 or PP- 1 , 100 mM (10 eq.)…”
Section: Resultsmentioning
confidence: 99%
“…All four conformers are significantly populated in equilibrium (0.05 < p i < 0.59). Many theoretical studies on the origin of stereoselectivity in Michael additions take these four conformational degrees of freedom into account, but neglect the conformational diversity which quickly emerges for larger C(2) and N(1) substituents. A large number of rotatable bonds in the C(2) and N(1) substituents can give rise to a large number of stable conformers ( e.g ., over 200 for 6e ).…”
Section: Resultsmentioning
confidence: 99%